AnswerRank: Identifying Right Answers in QA system - Geerthik S; Venkatraman S; Rajiv Gandhi K (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Ranking of answers in Community CQA (CQA) is most important task in finding best answer, which depends on type of question and relevance of answer to the question. If a question is posted in a CQA site it will get multiple answers in different views. It is the responsibility of a CQA system to identify best answers and make them display as top answers. For identifying the best answers different ranking techniques for finding the top answers are used. The main two problems we identify in the CQA sites are most of the best answers identified by CQA sites are from the users who had many followers. Also if a question is posted and if the best answer is written by a user late after many answers, the probability of the answer to be get ranked as top answer with highest upvotes is very less. This paper describes AnswerRank a method to rank the answers provided by the users in CQA sites. The AnswerRank method of ranking treats users with more followers and less followers equally. Also the answer written at various time intervals by different users are also treated equally. Only ranking is based on quality of answers. We compare AnswerRank method with existing ranking methods .The experimental results shows that our approach is best method in ranking Community CQA sites.